PELAKSANAAN PENDIDIKAN POLITIK BAGI MASYARAKAT OLEH PARTAI POLITIK KOTA PEKANBARU BERDASARKAN UNDANG-UNDANG NOMOR 2 TAHUN 2011 TENTANG PARTAI POLITIK - Yolanda Melisa; Emilda Firdaus; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Law of the Republic of Indonesia Number 2 of 2011 concerning Political Parties regulates the implementation of political education that must be carried out continuously by political parties. But in fact, the level of voter participation in the city of Pekanbaru is very low and the function of political parties is only carried out by members who wish to become legislative candidates or executive candidates in general elections. Based on this problem, the identification of problems in this thesis are: first, how is the implementation of political education for the community by political parties? Second, what are the obstacles and efforts in carrying out political education for the people by political parties?This research is a sociological and descriptive legal research. This research is located in the Regional Representative Office of the Functional Party in Pekanbaru, the Prosperous Justice Party Regional Representative Office in Pekanbaru, the Office of the Indonesian Democratic Party of Struggle's Branch Office in Pekanbaru, the Office of the Greater Indonesian Party Movement Branch Office in Pekanbaru, and the Office of the Leadership Council Branch of the People's Democratic Party in Pekanbaru. The data used consists of primary data and secondary data. Technical data were collected by field studies (interviews and questions and literature studies). Then analyzed qualitatively and make conclusions with deductive thinking methods.Based on this research, as a result we know that political parties do not have specific rules in carrying out political education and political parties have not been effective in carrying out their functions as organizers of political education. There are many challenges such as lack of public participation and the emergence of negative thoughts towards the party. The effort made is to build good relations with NGOs and educate the public mind.Key Word : Political Education – Community – Political Party